2003
DOI: 10.1159/000071817
|View full text |Cite
|
Sign up to set email alerts
|

GDNF Acutely Potentiates Ca<sup>2+</sup> Channels and Excitatory Synaptic Transmission in Midbrain Dopaminergic Neurons

Abstract: Glial cell line-derived neurotrophic factor (GDNF) is best known for its long-term survival effect on dopaminergic neurons in the ventral midbrain. A recent study showed that acute application of GDNF to these neurons suppresses A-type potassium channels and potentiates neuronal excitability. Here we have characterized the acute effects of GDNF on Ca2+ channels and synaptic transmission. GDNF rapidly and reversibly potentiated the high voltage-activated (HVA) Ca2+ channel currents in cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…This enhancement of dopamine synthesis likely leads to an increase in quantal release as observed in postnatal dopaminergic neurons in culture (Pothos et al, 1998). Furthermore, GDNF increases dopamine release owing to the enhancement of the excitability of midbrain dopaminergic neurons, which is associated with the inhibition of A-type K + channels (Yang et al, 2001), and potentiates the activation of Ca 2+ channels and excitatory transmission in midbrain neurons (Wang et al, 2003). The neuroprotective effects of exercise on the nigrostriatal system might also be due to other neurotrophic factors, which are known to be up-regulated by exercise and to ameliorate damage in other brain areas, as BDNF and FGF-2 in the hippocampus (Neeper et al, 1995;Gomez-Pinilla et al, 1997;Cotman and Berchtold, 2002).…”
Section: Physical Exercise and Gdnf Expression In The Nigrostriatal Smentioning
confidence: 98%
See 1 more Smart Citation
“…This enhancement of dopamine synthesis likely leads to an increase in quantal release as observed in postnatal dopaminergic neurons in culture (Pothos et al, 1998). Furthermore, GDNF increases dopamine release owing to the enhancement of the excitability of midbrain dopaminergic neurons, which is associated with the inhibition of A-type K + channels (Yang et al, 2001), and potentiates the activation of Ca 2+ channels and excitatory transmission in midbrain neurons (Wang et al, 2003). The neuroprotective effects of exercise on the nigrostriatal system might also be due to other neurotrophic factors, which are known to be up-regulated by exercise and to ameliorate damage in other brain areas, as BDNF and FGF-2 in the hippocampus (Neeper et al, 1995;Gomez-Pinilla et al, 1997;Cotman and Berchtold, 2002).…”
Section: Physical Exercise and Gdnf Expression In The Nigrostriatal Smentioning
confidence: 98%
“…GDNF enhances the excitability of midbrain dopaminergic neurons by inhibiting A-type K + channels, a fast action mediated by MAPK activation (Yang et al, 2001). GDNF also potentiates the activation of Ca 2+ channels and excitatory transmission in midbrain neurons (Wang et al, 2003). In addition, it was reported that long-term treatment of neuromus- binding protein frequenin (Wang et al, 2001a).…”
Section: Gdnf From Regulation To Functionmentioning
confidence: 99%
“…Differentiation of neuroendocrine PC12 cells with glucocorticoids increased the expression of VSCC, thereby enhancing the frequency of depolarization-induced exocytosis [206]. Additionally, GDNF rapidly and reversibly potentiates VSCC currents as well as exocytosis in cultured dopaminergic neurons [207].…”
Section: +mentioning
confidence: 99%
“…Though GDNF rapidly and reversibly potentiates voltage-activated Ca 2+ currents as well as the amplitude and frequency of spontaneous and evoked excitatory autaptic currents in dopaminergic neurons [207], GDNF is particularly noted for its delayed (days-weeks), long-term (days-weeks) effects, which occur even after a single administration. A single GDNF administration increases K + -evoked DA overflow throughout the striatum and in primary cultures of dopaminergic neurons, without affecting the release of GABA or the basal levels of DA [38,238,288].…”
Section: Endogenous and Exogenous Factors Modulating Catecholamine/damentioning
confidence: 99%
“…GDNF in particular has been studied extensively as a potential therapeutic agent for Parkinson's disease. Not only has GDNF been found to increase both the firing rate 45 and excitability 46,47 of dopamine neurons, but it has also been shown to be neuroprotective in virtually all neurotoxin--generated animal models of Parkinson's disease when injected directly into the substantia nigra or striatum 48 .…”
Section: Gdnf Therapy Of Parkinson's Diseasementioning
confidence: 99%